Design and Evaluation of a Hands-Free Video Game Controller for Individuals With Motor Impairments - Taheri , Atieh; Weissman , Ziv; Sra, Misha (Frontiers in Computer Science, 2021)
Over the past few decades, video gaming has evolved at a tremendous rate although game input methods have been slower to change. Game input methods continue to rely on two-handed control of the joystick and D-pad or the keyboard and mouse for simultaneously controlling player movement and camera actions. Bi-manual input poses a significant play impediment to those with severe motor impairments. In this work, we propose and evaluate a hands-free game input control method that uses real-time facial expression recognition. Through our novel input method, our goal is to enable and empower individuals with neurological and neuromuscular diseases, who may lack hand muscle control, to be able to independently play video games. To evaluate the usability and acceptance of our system, we conducted a remote user study with eight severely motor-impaired individuals. Our results indicate high user satisfaction and greater preference for our input system with participants rating the input system as easy to learn. With this work, we aim to highlight that facial expression recognition can be a valuable input method.